If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = -2(b + -3) + 8 Reorder the terms: 24 = -2(-3 + b) + 8 24 = (-3 * -2 + b * -2) + 8 24 = (6 + -2b) + 8 Reorder the terms: 24 = 6 + 8 + -2b Combine like terms: 6 + 8 = 14 24 = 14 + -2b Solving 24 = 14 + -2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '2b' to each side of the equation. 24 + 2b = 14 + -2b + 2b Combine like terms: -2b + 2b = 0 24 + 2b = 14 + 0 24 + 2b = 14 Add '-24' to each side of the equation. 24 + -24 + 2b = 14 + -24 Combine like terms: 24 + -24 = 0 0 + 2b = 14 + -24 2b = 14 + -24 Combine like terms: 14 + -24 = -10 2b = -10 Divide each side by '2'. b = -5 Simplifying b = -5
| 5x-10=3x+12 | | 4(z-2)+z=-13 | | 77-2x=2x+17 | | 5a-14=2a+7 | | M^2-36-16m=0 | | 2d=7(8) | | 3x-(4-2x)=12x+14 | | 4y+9-7y=-6 | | 9x^2-x-2=0 | | f(b)=3.75b+25 | | 3(x-2)=15 | | 5(x+2)=13 | | k+20=9k | | 6c+4-c=24 | | 4a+2=18 | | 64-2x=10x+16 | | -25=-x | | 5a=15(11) | | 2g+3g+5=0 | | 8z=54 | | 14t-8=6t | | -.833(9+2x)=40 | | -15=p+4p | | 3t=10 | | 25-3u=2u | | 3(s-10)=36 | | 4x-20=3x+16 | | 0.125x=9 | | 3x+15=10x-30 | | 3x^2-14x-49=0 | | 7-m=15 | | x+13=2x-19 |